Hepatocytic Differentiation Potential of Human Fetal Liver Mesenchymal Stem Cells: In Vitro and In Vivo Evaluation - Hoda El-Kehdy; Guillaume Pourcher; Wenwei Zhang; Zahia Hamidouche; Sylvie Goulinet-Mainot; Etienne Sokal; Pierre Charbord; Mustapha Najimi; Anne Dubart-Kupperschmitt (Stem Cells International)
In line with the search of effective stem cell population that would progress liver cell therapy and because the rate and differentiation potential of mesenchymal stem cells (MSC) decreases with age, the current study investigates the hepatogenic differentiation potential of human fetal liver MSCs (FL-MSCs). After isolation from 11-12 gestational weeks’ human fetal livers, FL-MSCs were shown to express characteristic markers such as CD73, CD90, and CD146 and to display adipocytic and osteoblastic differentiation potential. Thereafter, we explored their hepatocytic differentiation potential using the hepatogenic protocol applied for adult human liver mesenchymal cells. FL-MSCs differentiated in this way displayed significant features of hepatocyte-like cells as demonstrated in vitro by the upregulated expression of specific hepatocytic markers and the induction of metabolic functions including CYP3A4 activity, indocyanine green uptake/release, and glucose 6-phosphatase activity. Following transplantation, naive and differentiated FL-MSC were engrafted into the hepatic parenchyma of newborn immunodeficient mice and differentiated in situ. Hence, FL-MSCs appeared to be interesting candidates to investigate the liver development at the mesenchymal compartment level. Standardization of their isolation, expansion, and differentiation may also support their use for liver cell-based therapy development.